Testimony, A Tribute to Charlie Parker : With New and Selected Jazz Poems - Komunyakaa, Yusef (Book collections on Project MUSE., 2013)
Pulitzer Prize-winning poet Yusef Komunyakaa is well known for his jazz poetry, and this book is the first to bring together the verve and vitality of his oeuvre. The centerpiece of this volume is the libretto "Testimony." Paying homage to Charlie Parker, "Testimony" was commissioned for a radio drama with original music by eminent Australian composer and saxophonist Sandy Evans. Remarkably rich and evocative, encompassing a wide range of musical energy and performers, this moving affirmation of Parker's genius became a milestone in contemporary radio theater. Twenty-eight additional poems spa